L-selectin: A Major Regulator of Leukocyte Adhesion, Migration and Signaling - Ivetic, Aleksandar; Hoskins Green, Hannah Louise; Hart, Samuel James (Frontiers in Immunology, 2019)
L-selectin (CD62L) is a type-I transmembrane glycoprotein and cell adhesion molecule that is expressed on most circulating leukocytes. Since its identification in 1983, L-selectin has been extensively characterised as a tethering/rolling receptor. There is now mounting evidence in the literature to suggest that L-selectin plays a role in regulating monocyte protrusion during transendothelial migration (TEM). The N-terminal calcium-dependent (C-type) lectin domain of L-selectin interacts with numerous glycans, including sialyl Lewis X (sLex) for tethering/rolling and proteoglycans for TEM. Although the signals downstream of L-selectin-dependent adhesion are poorly understood, they will invariably involve the short 17 amino acid cytoplasmic tail. In this review we will detail the expression of L-selectin in different immune cell subsets, and its influence on cell behaviour. We will list some of the diverse glycans known to support L-selectin-dependent adhesion, within luminal and abluminal regions of the vessel wall. We will describe how each domain within L-selectin contributes to adhesion, migration and signal transduction. A significant focus on the L-selectin cytoplasmic tail and its proposed contribution to signalling via the ezrin-radixin-moesin (ERM) family of proteins will be outlined. Finally, we will discuss how ectodomain shedding of L-selectin during monocyte TEM is essential for the establishment of front-back cell polarity, bestowing emigrated cells the capacity to chemotax towards sites of damage.